Pengembangan dan Validasi Instrumen Analisis Buku Tematik-Terpadu pada Kurikulum 2013 - 'Alia Nur Husna Afandi; Kukuh Andri Aka (Jurnal Pendidikan Dasar Nusantara, 2019)
The purpose of the research in this article is to develop and validate an integrated book analysis instrument that discusses theoretical studies (1) characteristics of integrated learning, (2) scientific approach, and (3) textbook principles. The method in this study is; (1) studies the related theoretical studies used in integrated thematic books; (2) develop instrument lines consisting of variables, sub variables, and indicators; (3) develope scoring rubrics and instrument criteria, (4) validation to experts; (5) product improvements and final results. Through validation the expert concludes that the categories are valid and can be used.